Implementasi Hygiene dan Sanitasi di Kantin Kopikir Ika Universitas Mulawarman - Utoro, Panggulu Ahmad Ramadhani; Didimus, Destian (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2024)
Food is a necessity for humans, yet cases of food poisoning and infectious diseases related to food continue to rise. Contributing factors include poor personal hygiene, inadequate food handling, and unclean equipment. Food vendors often lack educational backgrounds in hygiene and sanitation, which affects the quality of the dishes they serve. This community service initiative emphasizes the importance of implementing hygiene and sanitation practices in the Kopikir Ika canteen at Mulawarman University. The methods used include socialization, observation, and education for the canteen operators. The results show increased awareness and understanding of the operators regarding the importance of hygiene and sanitation, as well as the steps taken to improve cleanliness standards in the canteen and the quality of the food products served.